(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2011)
This retrospective study was conducted on 145 postmortem cases of hanging victims at government medical college morgue over a period of two years. The objective of this study was to find out the pattern of hanging cases as a proper method of suicide and to evaluate the present situation of hanging in this capital city. Out of 145 cases, 41% were male and 51% were married. One hundred and one victims hanged themselves at night, while 44 at day time. In 72 victims, stomachs were found empty. Most (97%) of the bodies were recovered from inside the living rooms. Ninety seven percent had complete suspension. One hundred and forty two (98%) cases had ligature mark in neck. Thirty nine cases had fracture of hyoid bones, 27 cases had fracture of thyroid cartilages. Most of the victims (45%) were from the age group 20- 30 years. Dopatta (orna) was the commonest (35%) ligature material. Quarrel among husband and wife was the commonest (31%) cause of suicidal hanging. Hanging was observed as a frequently used method of suicide in Bangladesh. Key words: Hanging, suicide; post mortem DOI: 10.3329/jafmc.v6i2.7273 JAFMC Bangladesh. Vol 6, No 2 (December) 2010 pp.37-39